FORGOTTEN ECHOES: SUFFERING, SILENCE IN THE STORIES OF WOMEN IN ARUPA PATANGIA KALITA’S NARRATIVE - Singha, Aradhana; Bora, Manashi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this paper is to analyze the suffering, violence and silence that prevail in Kalita’s oeuvre. Discussing the characters and their circumstances in her works allows us to witness how they traverse their distress, and their dichotomy of conflict, loss, and hope. In addition, these themes are explored in order to provide implications regarding human experience and endurance in the face of adversity on a larger scale. In her work, Kalita implores readers to look where strength and weakness can meet and what being human looks like in a world where it appears that chaos and violence reign. By carefully examining her writings, we are able to uncover the layers of meaning in her storytelling and in her commentary of the cultural and social scenario during a difficult time in Assam. Therefore, this study takes insight into her themes of loss, suffering and silence and makes this discourse a pivotal task in aiding the comprehension of the contemporary Assamese literature and its visions on its society.